Effect of an In-Home Palivizumab Administration Program for Children with Medical Complexity - Hina Emanuel; Aravind Yadav; Julie C. Eapan; Maria Caldas-Vasquez; Tomika S. Harris; Katrina McBeth; Fatima Boricha; Janice John; Ivan G. Magana Ceballos; Giuseppe N. Colasurdo; Maria E. Tellez; Tina Reddy; et al. (MDPI AG, 2024)
Background: In-home palivizumab administration programs (PH) have shown promise in reducing RSV-associated infections. These programs may be particularly beneficial for children with medical complexity (CMC) by limiting their exposure to healthcare-associated infections (HAIs) from non-RSV-related pathogens during transportation and visits to medical facilities. Methods: In this prospective study, 41 children with CMC less than 2 years of age were randomized by their health insurance to receive PH or in the clinic (PC) during the RSV season (October 2018-April 2019). Patients were stratified by home ventilation. The primary outcome was the total number of face-to-face encounters. Secondary outcomes were unscheduled clinic visits and hospitalizations secondary to the non-RSV LRTIs. Standard frequentist and Bayesian analyses were performed. Results: All demographic factors and strata were matched between PH ("n" = 13, mean age 22 mo. SD ± 1), and PC ("n" = 28, mean age: 18 mo. SD ± 1). There was a decrease in the number of total face-to-face encounters (adjusted for mechanical ventilation and baseline diagnosis) [(4.5 vs. 8.8), (RR: 1.8, 95% CI: 1.3-2.5, p = 0.001)], and hospitalizations [(0.3 vs. 1.25), (RR: 3.8, 95% CI: 1.3-11.3, p = 0.016)], in the PH vs PC groups. Bayesian analysis showed a 93% probability of benefit in favor of fewer face-to-face encounters in the PH group. Conclusions: This study suggests that PH administration may reduce healthcare utilization in CMC. Minimizing exposure to healthcare facilities and supporting home-based interventions are promising strategies for this population.